Fabrication of microfluidic droplet former II. - Yew, Jeanette Si Yang. (2012)
The micro-scale industry is booming as time passes. This encourages development in micro-research such as microfluidic and microstructures. In this project, we carried out fabrication to produce microchips and PDMS stamps that is able to simulate droplet generation. This simulation is aimed towards achieving cell encapsulation in future developments. As an introduction, the main but different microfluidic properties which include Stokes flow, electrostatic forces and surface tension were analyzed and simple calculations can be carried out with the use of some mathematical equations. The different soft lithography techniques were also given a short description along with the elaboration of their methodology. This enables comparison between the different techniques and with microcontact printing being the simplest and most common, it was being carried out in this project. The fabrication process was the main experimental component in this project. Fabricated microchips and PDMS produced were then being tested on to determine the success and at the same time, changes were implemented in the process to ensure better results were obtained. The details are better elaborated as follows.